English as a Foreign Language Teachers’ Identity and Motivation: The Role of Mindfulness - Zhu, Dianyong (Frontiers in Psychology, 2022)
Teaching is a career with a high rate of anxiety and burnout in all phases of teaching with specific challenges related to the feature of language education. The concept of motivation can be an important basic mechanism since educators who are not motivated are distressed because of the anxious characteristic of the education profession. Moreover, educator identity is a new issue that has built a perspective to examine educators’ growth by thinking about who they are as well as how they perform what they perform in a specific situation. Recently, programs that are based on mindfulness are known as efficient interventions enhancing motivation and decreasing tension in people. Given the prominence of mindfulness in educational settings and its neglected role in foreign language learning, the contemporary review attempts to inspect the function of mindfulness on English as a foreign language (EFL) teachers’ motivation and identity. Subsequently, some pedagogical recommendations for the educational representatives such as teachers and teacher trainers are offered.